"STUDYING THE "OTHER": CHALLENGES AND PROSPECTS OF MUSLIM SCHOLARSHIP IN SOUTHEAST ASIA" - Yousif, Ahmad Fadil (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
In institutions of higher learning in the Muslim world, in contrast to similar institutions in Western countries, scant attention is paid to the field of religious studies (comparative religion). This, however, was not always the case. Between the ninth and twelfth centuries, Islamic civilization witnessed the rise—and also eclipse—of the discipline of ‘Ilm a- Milal wal n-Nihal (literally, “knowledge of religious groups and sects”). As in the early Islamic era, today Muslims scholars and students face several challenges in their study of world religions. Some of these challenges are common to Muslim and Western intellectuals on the subject, while others are peculiar to Muslim scholarship. They range from the challenge of defining and delimiting the field to those associated with methodology. This presentation examines some of these challenges, drawing upon classical Islamic heritage, experience of Western comparativists, and works of modern Muslim scholars in the field. It will deal with the question: Why do Muslim scholars need to make a serious study of major world religions? Interestingly, some Muslims are opposed to such an intellectual exercise, arguing that it will do more harm than good. It is, therefore, necessary to ask again: What led Muslim scholars, especially in the past, to study world religions . ​